Dynamic experimental investigation on the volatilization behavior of lead and cadmium in the simulated Municipal Solid Waste (MSW) influenced by sulfur compounds during incineration - Liu, Changqi; Huang, Yaji; Wang, Xinye; Zhang, Shuaiyi; Xia, Wenqing; Sun, Chenggong; Liu, Hao (American Chemical Society, 2017)
In China, coal, often with a high level of sulfur, is always mixed with municipal solid waste (MSW) in waste incineration plants due to the low heating value and high moisture content of MSW. The influence of sulfur compounds on the volatilization of heavy metals in MSW is of great concern for China’s waste incineration plants. In this study, the continuous dynamic volatilization process of Pb and Cd is investigated by adding different forms of sulfur compounds, elemental sulfur (S), and sodium sulfate (Na2SO4), to the simulated MSW in a laboratory incinerator, at both 1 and 3 wt %, respectively. The experimental results show that the added S begins to affect the volatilization of Pb and Cd at about 700 °C; adding S can lead up to 49.6% reduction in the volatilization of Pb, as the produced sulfur dioxide is promoting the formation of a condensed sulfate phase, and part of Pb is fixed in the form of PbS in the bottom ash. But for Cd, adding S causes up to 15.9% increase in its volatilization as S seizes part of O2 in the air, which is conducive to forming the reducing atmosphere. In the reducing atmosphere, CdO can be easily reduced to Cd, which volatilizes more easily than CdO at high temperatures. In fact, in the reducing atmosphere, the volatilization of Cd far outweighs the volatilization of Pb at 700–800 °C. On the other hand, adding Na2SO4 almost has no influence on the volatilization of lead and cadmium below 900 °C.